Study of Social Media Marketing Activities and its impact on the Consumer Based Brand Equity and Purchase Intention for White goods brands (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Social Media has become the most important tool  for interpersonal interactions in today’s world and  its application has led the human interaction to  assume greater magnitude, impacting everything  around us. The world of business and commerce  has also seen opportunities in this field and  most importantly the Marketing area sees it  as a platform to reach consumers effectively.  Various researches have shown that social media  marketing (SMM) efforts are effective in building  the Consumer based brand equity (CBBE) and  Purchase intention (PI) of the consumers and this  indicates the role of cyber world in marketing  area. The digital marketing and social media  marketing are the new age media tools that have  revolutionized the marketing scenario.  Although there are numerous researches on the  impact of SMM, but there is nothing specific to  understand its impact on White goods brands and  this gap area has been addressed through literature  review and conceptual understanding of terms  Social Media Marketing, Consumer Based Brand  Equity, Purchase Intention and also researches  done for other industries.
Keywords: Social Media; Social media marketing; Consumer based brand equity; Purchase Intention; CBBE; PI; White Goods; Honeycomb model